Partitioning of Ti and kinetic growth predictions on the thermally grown chromia scale of a polycrystalline nickel-based superalloy - Pedrazzini, S; Rowlands, B; Turk, A; Parr, I; Hardy, M; Bagot, P; Moody, M; Galindo-Nava, E; Stone, H (Springer, 2019)
Titanium is commonly added to nickel superalloys but has a well-documented detrimental effect on oxidation resistance. The present work constitutes the first atomistic-scale quantitative measurements of grain boundary and bulk compositions in the oxide scale of a current generation polycrystalline nickel superalloy performed through atom probe tomography. Titanium was found to be particularly detrimental to oxide scale growth through grain boundary diffusion.